(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
This study aims to analyze the effects of economic growth, education, and health on the Human Development Index (HDI) in five regencies of the Mainland Timor region, namely Kupang Regency, South Central Timor, North Central Timor, Belu, and Malaka, both partially and simultaneously. This study employs a quantitative approach using secondary data obtained from publications of BPS-Statistics Indonesia of East Nusa Tenggara Province and the respective regency-level BPS offices for the 2018–2023 period. The study uses 30 panel data observations derived from five regencies over six years. The data were analyzed using panel data regression with EViews 12. The estimation model was selected through the Chow test, Hausman test, and Lagrange Multiplier test, with the Random Effect Model (REM) identified as the most appropriate model. The results show that economic growth has a negative and statistically insignificant relationship with HDI. Education, measured by Expected Years of Schooling, has a positive and significant effect on HDI, while health, measured by Life Expectancy, has a positive but statistically insignificant effect at the 5 percent significance level. Simultaneously, economic growth, education, and health significantly affect HDI, with an F-statistic of 6.009 and a probability value of 0.003. The R² value of 0.409 indicates that 40.9 percent of the variation in HDI can be explained by the model, while the Adjusted R² value of 0.341 indicates that the adjusted explanatory power of the model is 34.1 percent. These findings suggest that improving HDI in the Mainland Timor region should focus on strengthening education, enhancing health services, and promoting more inclusive economic growth